2010
DOI: 10.3998/ark.5550190.0012.804
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed selective cycloaddition of diazo compounds to [60]fullerene

Abstract: Dedicated to Professor Usein M. Dzhemilev on the occasion of his 65th birthday AbstractThe effective catalytic method for cycloaddition of higher diazoalkanes and diazoacetates to [60]fullerene in the presence of the three-component catalytic system Pd(acac) 2 -PPh 3 -Et 3 Al has been developed. The yield and selective formation of the target homo-and methanofullerenes are dependent upon the structure of the original diazo compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…It was found that in the interaction of C 60 -fullerene with a 1.5-fold excess of 2-diazo-3-(pentylthiomethyl)-or 2-diazo-3-(cyclohexylthiomethyl)butane, generated in situ by the oxidation of hydrazones of the corresponding ketones, in the presence of 20 mol% of the three-component catalyst Pd(acac) 2 -PPh 3 -Et 3 Al (1:2:4) at room temperature (18-20 • C) in chlorobenzene, the corresponding homofullerenes 1 and 2 are formed in 1 h with a yield of ~50% [21] (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that in the interaction of C 60 -fullerene with a 1.5-fold excess of 2-diazo-3-(pentylthiomethyl)-or 2-diazo-3-(cyclohexylthiomethyl)butane, generated in situ by the oxidation of hydrazones of the corresponding ketones, in the presence of 20 mol% of the three-component catalyst Pd(acac) 2 -PPh 3 -Et 3 Al (1:2:4) at room temperature (18-20 • C) in chlorobenzene, the corresponding homofullerenes 1 and 2 are formed in 1 h with a yield of ~50% [21] (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that in the interaction of C60-fullerene with a 1.5-fold excess of 2-diazo-3-(pentylthiomethyl)-or 2-diazo-3-(cyclohexylthiomethyl)butane, generated in situ by the oxidation of hydrazones of the corresponding ketones, in the presence of 20 mol .% of the three-component catalyst Pd(acac)2-PPh3-Et3Al (1:2:4) at room temperature (18-20°C) in chlorobenzene, the corresponding homofullerenes 1 and 2 are formed in 1 h with a yield of ~50% [21] (Scheme 1). Under the developed optimal conditions (~20-22 °C, 1 h, 20 mol.% Pd(acac)2-PPh3-Et3Al (1:2:4)), the cycloaddition of sulfur-containing diazoalkanes generated in situ from hydrazones of 4-methylthiobenzaldehyde and 2-acetylthiophene to C60-fullerene leads to compounds 3 and 4 in 50 and 45% yields, respectively (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diazoacetates containing cholesterol in the ester group [23], α-tocopherol, Trolox methyl esters, 20.29-dehydrobetulic, and ursolic acids [24], which have antioxidant, antitumor, and antiviral properties, were used as the initial pharmacological objects of the study. It has been shown that the above diazo compounds interact with C 60 -fullerene (molar ratio 5:1) in the presence of 20 mol.% of the three-component catalyst Pd(acac) 2 -PPh 3 -Et 3 Al, taken in a ratio of 1:4:4 at 80 • C, for 1 h in 1,2-dichlorobenzene, the corresponding methanofullerenes 1-5 are selectively formed with a yield of 60-75% (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…They employed Pd(OAc) 2 in the reaction of ethereal diazomethane with C 60 at 0 °C and isolated the methanofullerene in 15% yield. Tuktarov and co-workers developed three-component catalytic systems Pd(acac) 2 –PPh 3 –Et 3 Al to improve the efficiencies of cycloadditions. The formation ratio of the adducts depends on the substituents of the diazo compounds they used and the reaction conditions. When diazoesters or diazoketones were used for the three-component Pd(acac) 2 –4PPh 3 –4Et 3 Al catalytic reactions, [6,6] closed methanofullerenes were obtained exclusively in 30–60% yields.…”
Section: Carbene Addition To Empty Fullerenesmentioning
confidence: 99%